2018
DOI: 10.1016/j.jpowsour.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional characterization of nickel coarsening in solid oxide cells via ex-situ ptychographic nano-tomography

Abstract: J. R. (2018). Three dimensional characterization of nickel coarsening in solid oxide cells via ex-situ ptychographic nano-tomography. Journal of Power Sources, 383, 72-79. https://doi. AbstractNickel coarsening is considered a significant cause of solid oxide cell (SOC) performance degradation.Therefore, understanding the morphological changes in the nickel-yttria stabilized zirconia (Ni-YSZ) fuel electrode is crucial for the wide spread usage of SOC technology. This paper reports a study of the initial 3D mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 49 publications
(57 reference statements)
2
40
0
Order By: Relevance
“…The probable cause of the anisotropy is the nickel particles coarsening [37][38][39] and migration that was observed in our previous research [23,24,40] as well as by other research groups [18,41]. During the long-term operation, nickel particles migrate from the anode electrolyte interface toward the anode surface.…”
Section: Resultsmentioning
confidence: 92%
“…The probable cause of the anisotropy is the nickel particles coarsening [37][38][39] and migration that was observed in our previous research [23,24,40] as well as by other research groups [18,41]. During the long-term operation, nickel particles migrate from the anode electrolyte interface toward the anode surface.…”
Section: Resultsmentioning
confidence: 92%
“…The effect of this process will lead to the disconnection of pathways connected through small bottlenecks while a more stable behavior during operation will be observed for wider pathways characterized by low curvature resulting in an overall decrease in percolation but an increase of the characteristic pathway diameter for the remaining Ni pathways. De Angelis et al [46] used x-ray tomography for investigating Ni/YSZ cermets evolution. They observed that nickel coarsening leads to a loss of nickel connectivity and an improvement in connectivity through the pore phase.…”
Section: Discussionmentioning
confidence: 99%
“…This latter phenomenon represents a significant contribution to the global cell degradation [19]. Indeed, it has been shown that the Ni-YSZ cermet is subjected under operation to a Ni agglomeration resulting in a phase coarsening and a migration changing the Ni distribution in the electrode [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%